EFEKTIFITAS PELAKSANAAN FUNGSI INTELIJEN KEIMIGRASIAN TERHADAP PENYALAHGUNAAN IZIN TINGGAL KUNJUNGAN DI KANTOR IMIGRASI KELAS I TPI PALEMBANG - M. Aidil Al Apip; M. Alvi Syahrin; Tony Mirwanto (Journal of Administration and International Development, 2022)
The number of immigration violations at the Immigration Office Class I TPI Palembang has increased every year. There is an increase in immigration action for foreigners holding Visa Residence Permit (VRP) from 2018 to 2019 around 86%. When viewed from the point of view of legal effectiveness, it can be influenced by several things, namely law enforcement, facilities and facilities, culture, society and even the law itself. The author focuses on this paper to provide an overview through field research, from the implementation of immigration intelligence tasks and their influence in reducing the number of immigration violations, especially on violations of residence permit abuse in the work area of ​​the Immigration Office Class I TPI Palembang. This study uses a normative-empirical approach. This study resulted in the following discussion analysis. The implementation of the immigration intelligence function against the misuse of VRP in the Immigration Office Class I TPI Palembang has not been effective in terms of the results of the implementation and management of the implementation of the intelligence operations carried out. This is because in terms of the implementation of immigration intelligence operations, it has not shown maximum achievements in the form of early detection of immigration violations, both VRP violations and other immigration violations through intelligence operations in the Immigration Class I TPI Palembang area. This is influenced by the condition of a large area, limited human resources, and inadequate infrastructure. Factors that affect the effectiveness of the results of the implementation of immigration intelligence operations against the abuse of VRP and the management of the implementation of intelligence operations against the abuse of VRP in the Immigration Office Class I TPI Palembang are legal factors that are not adequate in providing technical rules for implementation in the field, law enforcement factors are still lacking in implementation immigration intelligence because the nomenclature is new, and the supporting facilities and infrastructure are not maximized, as well as society and culture that still does not support the implementation of immigration intelligence.